6(5-2x)-2x=86

Simple and best practice solution for 6(5-2x)-2x=86 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(5-2x)-2x=86 equation:


Simplifying
6(5 + -2x) + -2x = 86
(5 * 6 + -2x * 6) + -2x = 86
(30 + -12x) + -2x = 86

Combine like terms: -12x + -2x = -14x
30 + -14x = 86

Solving
30 + -14x = 86

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -14x = 86 + -30

Combine like terms: 30 + -30 = 0
0 + -14x = 86 + -30
-14x = 86 + -30

Combine like terms: 86 + -30 = 56
-14x = 56

Divide each side by '-14'.
x = -4

Simplifying
x = -4

See similar equations:

| 4z^2+52z=0 | | 18p+90= | | 4x+472=9 | | 3x-[(2x+5)-2(x+3)]+4+x^2=(x+3)(x-5) | | -18=7k+2k | | 17-20x=(-13-5x).4 | | 110+3x-8+3x+6=102 | | 2(m-5)x+2=0 | | 9[w+8]=-7w-24 | | -29=-4x-3(-2x+15) | | 8(j+5)=6 | | 1(x+2)=-3x | | 0+y=11 | | 6g-(g-7)=132 | | -9x-19=-199 | | 23x=60x | | 5(4-2k)-4K=90 | | 6xy-7xy+8x+3=-6y+6 | | 4.8-9.6x= | | 4.50+2.25n=31.50 | | y=3.1x-0.1 | | -5c+4=4 | | -x-3+x=2x-7 | | (1n-8)-(-2+2)= | | -2-6(6b+5)=-248 | | 30+0.25x=59.5 | | 7-4w= | | 3(2+y)-4v=v+16 | | 4(8p-3)= | | -3+15=-3t+5t | | 30.00+0.25x=59.5 | | 7x=4x+50 |

Equations solver categories